Qi-Deficiency Related Increases in Disease Susceptibility Are Potentially Mediated by the Intestinal Microbiota. (23rd October 2018) - Ma, Ke; Chen, Jieyu; Kuang, Liuyan; Bi, Jianlu; Cheng, Jingru; Li, Fei; Sun, Xiaomin; Nie, Xiaoli; Liu, Yanyan; Luo, Ren; Zhao, Xiaoshan
Abstract : Qi-deficiency (QX) is thought to promote the body's susceptibility to disease, but the underlying mechanism through which this occurs is not clear. We surveyed the traditional Chinese medicine constitution (TCMC) of healthy college students to identify those that were PH (balanced TCMC constitution) and QX (unbalanced TCMC constitution). We then used high-throughput sequencing of the 16SrRNA V3-4 region in fecal microbiota samples to identify differences between those obtained from PH and QX individuals. Our results demonstrated that the alpha diversity of QX samples was significantly lower than that of PH samples ( p < 0.05) and that beta diversity was remarkably different in QX and PH samples. Four and 122 bacterial taxa were significantly overrepresented in QX and PH groups, respectively. The genera Sphingobium, Clostridium, and Comamonas were enriched in the QX group and had a certain pathogenic role. The QX group also showed a statistically significant lack of probiotics and anti-inflammatory bacteria such as Bifidobacterium and Bdellovibrio . The functional potential of QX bacterial taxa was reduced in fatty acid metabolism and butanoate metabolism. We contend that the imbalanced intestinal microbiota in QX and the following functional changes in metabolism influence immunity and energy metabolism, which could increase susceptibility to disease.